Education and Responsible Research and Innovation (RRI): International Perspectives - Romero-Ariza, Marta (2017)
What kind of science education is required in a world deeply influenced by science and technology? How can we contribute to Responsible Research and Innovation (RRI) through science education? Are students and teachers prepared to address current socio-scientific challenges? What kinds of pedagogies foster the skills and values required for taking a critical position in the discussion of socio-scientific problems? Which teaching and learning activities prepare students to actively contribute to the development of smart and creative solutions? These and others are some of the key questions underlying this special issue devoted to education and RRI.